Evaluasi Penggunaan E-Learning dalam Pendidikan Ekonomi: Tinjauan Studi Literatur - Siswanto , Romi (Universitas Terbuka, 2023)
Abstract: This literature review aims to explore the influence of learning motivation on academic achievement in the subject of economics. Based on previous literature and research, learning motivation is considered an important factor in improving student academic performance. The Self-Determination theory, which emphasizes the importance of intrinsic motivation in improving academic performance, is also the theoretical foundation of this literature review. The research method used is a literature study by collecting and analyzing articles, journals, and books related to the influence of learning motivation on academic achievement in the subject of economics. The results of the literature review indicate that learning motivation has a significant influence on academic achievement in the subject of economics. The higher the student's learning motivation, the higher their academic performance in the subject of economics. Therefore, there is a need to make efforts to improve students' learning motivation in the subject of economics by considering factors that influence learning motivation, such as teaching methods, teacher quality, learning environment, and personal factors of students.